Suicidality in LGBTQ+ Youth. Issue 1 (1st January 2018) - Vaughan, Susan C.
ABSTRACT: In this paper I show the ways in which society, culture, family, and intrapsychic conflict come to play a role in the suicidal ideation and behavior of adolescents within the lesbian, gay, bisexual, transgender, queer plus intersex, asexual, pansexual, polyamorous (LGBTQ+) community. I touch on LGBTQ+ history, review risks such as suicidality that are higher in this population, and consider common developmental challenges to transgender children and adolescents. I then present a clinical vignette of a trans girl with newly emergent transgender feelings in puberty who became suicidal when she learned (prior to transition) that there was a spot on the girls' (but not the boys') volleyball team. I will try to show how twice-weekly psychodynamic psychotherapy was useful in creating a more resilient and solid identity in the face of lack of family acceptance and how judicious work with the family around medical issues related to transitioning contributed to the patient's well-being.